Penguatan Pendidikan Agama Islam Melalui Budaya Sekolah - Muhammad Sya'roni (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2021)
Many Islamic religious education experts criticize PAI learning in schools. PAI learning is lacking and has not been able to provide knowledge and shape the attitudes, personality, and skills of students maximally. For this reason, schools are required to innovate to develop and improve the quality of PAI learning in schools. Through a school culture which is full of Islamic teachings and values, PAI learning can be strengthened. so that it is able to realize the goals of National Education. Strengthening Islamic religious education through school culture can be creat by creating an Islamic atmosphere in schools, religious habituation activities, Islamic behavior of school residents, internalizing Islamic teachings and values ​​in the learning process and school activities.